Sosialisasi Peran Mangrove terhadap Kelimpahan Ikan di daerah Pelabuhan Belawan - Ewin Handoco Saragih; Welmar Olfan Basten Barat; Winfrontstein Naibaho (CERED Indonesia Publishing, 2022)
Mangrove forest is the element that plays the most role in balancing environmental quality and neutralizing pollutants. Mangrove ecosystems have an important role in the survival of living things both as providers of environmental services and meeting the needs of human life, mangrove ecosystems have ecological functions, namely as abrasion resistance, climate enlargement, economic function, as a livelihood for coastal communities, production of sharing forest products, resources building material. Damage to mangrove ecosystems can be caused by land conversion activities into other uses such as residential land, plantations, aquaculture, and tourism. This socialization of the role of mangroves in fish abundance is important to provide input to the community that the area around the mangrove has a function as a nursery area for fish seeds and also a fish house. This socialization is very useful for the community so that the community is aware of the importance of the role of mangroves for the abundance of fish related to the community's economy.